A Si‐CdTe Composite Quantum Dots Probe with Dual‐Wavelength Emission for Sensitively Monitoring Intracellular H2O2. (9th February 2022) - Zhou, Jialing; Zhao, Ruoxi; Du, Yaqian; Liu, Shikai; Li, Wenting; Gai, Shili; He, Fei; Feng, Lili; Yang, Piaoping
Abstract: Hydrogen peroxide is an important reactive oxygen species (ROS) that acts as a significant marker of oxidative stress in certain diseases. Owing to the autofluorescence of biological samples, H2 O2 monitoring remains challenging. Here, Si‐CdTe quantum dots (QDs) are prepared as novel ratiometric fluorescent probes prepared for sensitive detection of H2 O2 and glucose, the low detection limit of H2 O2 and glucose is 79 and 140 nm, respectively. In this article, CdTe QDs are combined with Si QDs to reduce the cytotoxicity of CdTe. The survival rate of HeLa cells remains at 80% after incubation with the Si‐CdTe QDs at a concentration of 500 µg mL −1 for 24 h. Fluorescence extinguishes based on 488 and 514 nm channels are used as internal references to avoid environmental interference and demonstrate selective H2 O2 biosensing. In addition, the probe has an excellent colocalization effect in the lysosome under the 514 nm channel, with a maximum Pearson coefficient of 0.96. The advantages of easy preparation, low toxicity, high resistance to photobleaching, and high specificity of the Si‐CdTe QDs probes provide a new and convenient means to monitor and detect changes in the endogenous intracellular H2 O2 concentration and to select 514 nm lysosomal colocalization dyes. Abstract : A dual‐channel fluorescence‐emitting Si‐CdTe QDs is prepared to colocalize in the lysosomes of tumor cells and ratiometric detection of H2 O2 due to oxidative stress under the special 514 nm channel. The Si‐CdTe QDs probe can accurately detect glucose in animal serum, with a relative standard deviation less than 3.00% ( n  = 3).